Perancangan Sistem Informasi Promosi dan Pemesanan Wedding Organizer Berbasis Web - Marchelina Marchelina; Fajriyah Fajriyah; Iwan Setiawan (Jurnal Minfo Polgan, 2026)
Wedding Organizer is one of the service fields related to wedding parties to form all wedding preparation activities. This Wedding Organizer provides various needs needed by the bride and groom including tents, chairs, delivery boxes, wedding decorations, wedding dresses and various other wedding packages needed. In the Wedding Organizer Pelaminan Hantaran Aulia service, there is a problem with the promotion and ordering system that is carried out. Where the dissemination of information in offering or promoting Wedding Organizers is incomplete using social media.